From Knowledge to Practice: A Critical Discourse Analysis of Teacher-Student Classroom Discourse - Sapkota, Chet Narayan; Mahatara Chhetry, Surendra Bahadur (Kalika Journal of Multidisciplinary Research, 2026)
Classroom discourse is not just a neutral communication channel but a dynamic space where knowledge, power, and identities are constantly negotiated. This study employs Ruth Wodak’s Discourse-Historical Approach (DHA) to analyze how language in classroom interactions connects theoretical knowledge with practical application. Data were gathered through classroom observations, audio-visual recordings, and semi-structured questionnaires with three secondary school teachers, teaching English, science, and social studies and thirty students in Nawalparasi, Nepal. The analysis uncovers how teachers’ linguistic strategies, such as questioning, turn-taking, nomination, and evaluation, both reinforce and challenge institutional hierarchies while shaping student engagement. Students are not passive; they actively influence meaning-making through negotiation, resistance, and co-construction. The study also takes a cognitive perspective by exploring how schemas, scripts, and frames influence discourse,illustrating how mental models guide interaction and interpretation. The results show that classroom communication both supports and questions existing beliefs and power structures, reflecting broader sociopolitical and historical processes. By integrating linguistic, cognitive, and socio-historical perspectives, this research provides a deeper understanding of classroom communication as a social practice. The study further suggests that raising discourse awareness among educators can promote participatory, inclusive and equitable teaching practices, ultimately linking theoretical insights to practical classroom experiences.